1992
DOI: 10.1007/bf02221678
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon, insulin and somatostatin secretion in response to sympathetic neural activation in streptozotocin-induced diabetic rats. A study with the isolated perfused rat pancreas in vitro

Abstract: Summary. Changes in glucagon, insulin and somatostatin secretion induced by electrical splanchnic nerve stimulation were examined in rats treated with streptozotocin as neonates and as adults. In order to study the direct neural effects we used the isolated perfused rat pancreas with intact left splanchnic nerve in vitro. In normal rats splanchnic nerve stimulation causes significant decreases in insulin (30-40%) and somatostatin (30-50%) secretion at both 16.7 mmol/1 and 1 mmol/1 glucose concentrations. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Two of the five doses of 6-OHDA produced degrees of islet sympathetic nerve terminal loss that bracketed the 65% loss seen in BB D. Importantly, the corresponding glucagon impairments during SNS of these two groups also bracketed the 57% impairment seen in BB D. Thus we conclude that the glucagon impairment during SNS in BB D is due to their islet nerve terminal loss and that the ␤-cell loss and hyperglycemia present in BB D had little additional effect. Previous data are consistent with this conclusion, as streptozotocin diabetes, which leaves islet nerve terminals intact, does not lead to an early impairment of the glucagon response to SNS in the isolated pancreas perfused with high glucose (28). We hypothesized that spontaneous islet nerve terminal destruction in BB D impaired the glucagon response to SNS by decreasing neurotransmitter release at the ␣-cell.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Two of the five doses of 6-OHDA produced degrees of islet sympathetic nerve terminal loss that bracketed the 65% loss seen in BB D. Importantly, the corresponding glucagon impairments during SNS of these two groups also bracketed the 57% impairment seen in BB D. Thus we conclude that the glucagon impairment during SNS in BB D is due to their islet nerve terminal loss and that the ␤-cell loss and hyperglycemia present in BB D had little additional effect. Previous data are consistent with this conclusion, as streptozotocin diabetes, which leaves islet nerve terminals intact, does not lead to an early impairment of the glucagon response to SNS in the isolated pancreas perfused with high glucose (28). We hypothesized that spontaneous islet nerve terminal destruction in BB D impaired the glucagon response to SNS by decreasing neurotransmitter release at the ␣-cell.…”
Section: Discussionsupporting
confidence: 74%
“…However, clinically significant DAN takes months to develop in rodents (28,30) and years to decades in humans (24). Because the glucagon response to insulin-induced hypoglycemia in the BB rat is severely impaired far earlier than the development of DAN (7), we considered it unlikely that DAN was the mediator of this specific, early glucagon impairment.…”
mentioning
confidence: 99%
“…4b), consistent with p r e v i o u s r e p o r t s [ 2 ] . I n r e s p o n s e t o f a s t i n g , hyperglucagonaemia was diminished in STZ-vehicle mice, potentially indicative of an impaired stimulated-glucagon response as has been shown for STZ-diabetic animals [17,18], whereas STZ-leptin mice had a non-significant trend towards increased glucagon levels compared with non-fasted levels. As corticosterone is implicated in the glucose-lowering action Time post pump (days) Fig.…”
Section: Resultsmentioning
confidence: 72%
“…On the other hand, it reveals a close interaction between the parasympathetic and sympathetic motor nuclei, which may provide, in addition to the regulatory mechanisms at the level of the pancreas (Ahren and Taborsky, 1986;Kurose et al, 1992), the anatomic basis at the level of the CNS for the frequently observed cosecretion of insulin and glucagon (Steffens and Strubbe, 1983;Secchi et al, 1995;Taborsky et al, 1998).…”
Section: Discussionmentioning
confidence: 97%